Personality traits, stress appraisals and sleep in young elite athletes: A profile approach. Issue 9 (2nd September 2021) - Nédélec, Mathieu; Lienhart, Noémie; Martinent, Guillaume; Doron, Julie
Abstract: The aim of this study was to identify young elite athletes' personality profiles using a person-centred approach and to investigate whether the profiles significantly differ in stress and sleep. 260 athletes from a variety of sports completed a questionnaire package to assess neuroticism and conscientiousness traits, stress appraisals (i.e. intensity and directional interpretation of stress, challenge and threat appraisals), and various indicators of sleep (i.e. sleep quality, social jet lag, Ford insomnia response to stress test (FIRST)). A latent profile analysis (LPA) approach was used to identify personality profiles based on the scores of neuroticism and conscientiousness. A multivariate analysis of variance was performed to examine if the athletes belonging to different personality profiles differ on stress appraisals and indicators of sleep. Three profiles emerged: Maladaptive profile (high levels of conscientiousness and neuroticism); Highly adaptive profile (moderate level of conscientiousness and low level of neuroticism); Adaptive profile (high level of conscientiousness and moderate level of neuroticism). Results showed that athletes from the adaptive profile reported significantly lower scores of stress intensity and threat appraisal than those from other profiles. Athletes from the maladaptive profile reported significantly higher levels of FIRST than those from other profiles as well as worse sleep quality and lower levels of challenge appraisal than the athletes from the highly adaptive profile. These results suggest that investigating personality profile may be useful in identifying athletes at higher risk of stress sensitivity and worsening sleep that are likely to benefit from preventive actions (e.g. cognitive behavioural therapy interventions).